2022
DOI: 10.3389/fped.2022.707136
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Prognosis of Hyperbaric Oxygen as Adjuvant Therapy for Neonatal Hypoxic-Ischemic Encephalopathy: A Meta-Analysis Study

Abstract: BackgroundPreclinical and clinical evidence suggests that hyperbaric oxygen therapy (HBOT) may benefit newborns. The effectiveness of HBOT for neonatal hypoxic-ischemic encephalopathy (HIE) remains controversial. We conducted a meta-analysis to evaluate the efficacy and prognosis of HBOT in neonates with HIE.MethodsA systematic search of eight databases was performed for available articles published between January 1, 2015, and September 30, 2020, to identify randomized controlled clinical trials (RCTs) on HBO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
(35 reference statements)
0
5
0
1
Order By: Relevance
“…Unfortunately, similar reports regarding experimental birth asphyxia, including clinical trials, are scarce. Available evidence indicates that HBOT applied within a short window after the HI reduces brain damage in newborns ( 16 , 17 , 31 , 38 , 89 , 100 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, similar reports regarding experimental birth asphyxia, including clinical trials, are scarce. Available evidence indicates that HBOT applied within a short window after the HI reduces brain damage in newborns ( 16 , 17 , 31 , 38 , 89 , 100 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical studies described, in which HBOT was used, clinical improvement in the condition of newborns suffering from HI was assessed using multiple methods, such as ECG and transcutaneous oxygen monitoring during HBO session, outcome indicators such as total efficiency (clinical symptoms, signs, and craniocerebral computed tomography), neuronal sequelae, and the NABA score ( 89 , 98 ). The accumulated results of these studies indicate that the benefits of HBOT are obvious.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique restores the blood-brain barrier via cerebral vasoconstriction, decreasing cerebral blood flow and reducing cerebral hematoma, and simultaneously increasing oxygen supply to ischemic tissues ( 74 ). A meta-analysis study ( 75 ) pointed out that Hyperbaric oxygen therapy significantly improved the total efficiency of treatment for neonatal HIE patients and reduced the risk of sequelae, however, the underlying mechanism is not clear. One study ( 76 ) showed that the likelihood of neurological dysfunctions is lower in a HIBD neonatal rat model undergoing hyperbaric oxygen treatment, compared with controls, suggesting that this therapy may improve prognosis via neuroprotective effects.…”
Section: Therapeutic Measures For Neonatal Hibd To Promote Endogenous...mentioning
confidence: 99%